The three hundred: Msub-Vcirc relation - Srivastava, Atulit; Cui, Weiguang; Meneghetti, Massimo; Dave, Romeel; Knebe, Alexander; Ragagnin, Antonio; Giocoli, Carlo; Calura, Francesco; Despali, Giulia; Moscardini, Lauro; Yepes, Gustavo (Monthly notices of the Royal Astronomical Society, 2024)
In this study, we investigate a recent finding based on strong lensing observations, which suggests that the sub-haloes observed in clusters exhibit greater compactness compared to those predicted by ΛCDM simulations. To address this discrepancy, we compare the cumulative sub-halo mass function and the Msub–Vcirc relation between observed clusters and 324 simulated clusters from THE THREE HUNDRED project, focusing on the hydrodynamic resimulations using GADGET-X and GIZMO-SIMBA baryonic models. The cumulative sub-halo mass function of GIZMO-SIMBA simulated clusters aligns with observations, while GADGET-X simulations exhibit discrepancies in the lower sub-halo mass range, possibly due to its strong supernova feedback. Both GADGET-X and GIZMO-SIMBA simulations demonstrate a redshift evolution of the sub-halo mass function and the Vcirc function, with slightly fewer sub-haloes observed at lower redshifts. Neither the GADGET-X nor GIZMO-SIMBA (albeit a little closer) simulated clusters’ predictions for the Msub–Vcirc relation align with the observational result. Further investigations on the correlation between sub-halo/halo properties and the discrepancy in the Msub–Vcirc relation reveal that the sub-halo’s half mass radius and galaxy stellar age, the baryon fraction, and sub-halo distance from the cluster’s centre, as well as the halo relaxation state, play important roles on reproducing this relation. Nonetheless, challenges persist in accurately reproducing the observed Msub–Vcirc relationship within our current hydrodynamic cluster simulation that adheres to the standard ΛCDM cosmology. These challenges may stem from shortcomings in our baryon modelling, numerical intricacies within the simulation, or even potential limitations of the ΛCDM framework.
Im Text ist "sub" und "circ" tiefgestellt
Veröffentlicht: 31 January 2024
Gesehen am 25.11.2024